Trauma, History, and the Limits of Language - Tegla, Emanuela (European Scientific Journal, ESJ, 2018)
The question of adequate representation through words, of a proper correlation between object and word, signifier and signified, has always been at the forefront in literary studies. This conundrum has acquired new dimensions in the last century, due to the traumatic events that marked it and led to an irrepressible need to confess and bear witness, in fictional as well as in non-fictional form. This dimension of trauma has unsettled the relationship between what words are taken to represent and the reality they stem from, as well as the very possibility of putting in words certain realities denoting unspeakable individual or collective trauma. After a short theoretical introduction into the concept of trauma, the present essay will seek to analyse a number of instances, from prose, poetry and non-fiction writings, which exemplify the various dimensions of the difficulty of talking about trauma.